La negación de la ambigüedad: Transgénero en la España Barroca - Begoña Álvarez Seijo (Ambigua, 2017)
In Baroque Spain, the cases of change of roles, physical appearance and modes of behaviour typical of the socially constructed gender by the dominant ideology, Catholicism, were very abundant, especially in relation to women, but not condemned by the institutions in power as one might think. Hermaphroditism, androgyny, cross-dressing or transsexuality seem identities that have only recently found their place within postmodern societies; nothing could be further from the truth. With other denominations, based on other arguments or explanations, respected or condemned, for other reasons or for different purposes, all these categories or identities can be found in seventeenth-century Spain, within a directed and behaviourist culture as the Baroque. The present article aims to analyse, from all the levels of the dominant discourse of the time the meaning, the role and place that the intermediate identities occupy, and the reasons that lead to the controversy, during the XVI and XVII centuries, on the feminine "transmutations". Furthermore, this paper will analyse real examples, such as the one of Elena Céspedes or Catalina of Eraúso, (end of century XVI), and some others in the literatura de maravillas, with the mirabilia or miraculus defended by Antonio de Torquemada, Martin del Rio and Fray Antonio de Fuentelapeña, which was at the same time rejected as magicus or prodigium by other scholars and moralists of the time. All this in order to demonstrate how these identities, both accepted and denounced, are links of a chain socially constructed by the Counter Reformation and the State to justify the inferiority of the feminine gender and its necessary submission to man.